Developing Effective Communication Skills in Counseling: A Focus on Schizophrenia and Depression - Utami, Wahyu; Marwa, Mentari (Guidance and Counseling Study Program, Pattimura University, 2024)
This study evaluates the effectiveness of Social Skills Training (SST) on improving social interactions and reducing psychological symptoms in individuals with schizophrenia by comparing pre-test and post-test scores of control and experimental groups. The quasi-experimental research, using a static group comparison design, involved five male post-hospitalized schizophrenia patients aged 19-40 in Nganjuk Regency. The experimental group received SST, while the control group did not. Results from paired sample t-tests indicated no significant change in the control group but showed significant improvement in the experimental group, with post-test scores significantly lower than pre-test scores (p < 0.05). Independent sample t-tests confirmed no significant difference in pre-test scores between groups, but post-test scores revealed significant differences, affirming SST's positive impact. The SST intervention, comprising sessions on communication, friendship, joint activities, handling difficult situations, expressing opinions, and family psychoeducation, significantly enhanced social skills and reduced negative responses. These findings highlight SST as an effective intervention for individuals with mental health issues, promoting better social interactions and reducing relapse rates, thereby supporting its integration into therapeutic practices.